m5C RNA modification in colorectal cancer: mechanisms and therapeutic targets - Jiawei Wang; Cenyi Qi; Ran Wang; Yuepeng Cao; Yuping Zhou; Guoliang Ye (Journal of Translational Medicine)
Abstract 5-Methylcytosine (m5C), an important RNA modification, has been extensively studied in colorectal cancer (CRC). In recent years, with advances in high-throughput sequencing technology and RNA modification detection tools, the role of m5C modification in tumorigenesis and development has been gradually elucidated and regulated by “writers,” “erasers,” and “readers,” m5C modification affects many biological processes and cancer progression, including cell proliferation, autophagy, invasion, and apoptosis. In CRC, m5C modification affects cancer cell proliferation, migration, invasion, drug resistance, and immunotherapy resistance by regulating RNA stability, metabolic reprogramming, signalling pathway activation, and immune escape. Moreover, m5C modification provides potential biomarkers and targets for early diagnosis and efficacy prediction. In addition, studies on drugs that target m5C modification related proteins have shown that intervention in m5C modification may provide new directions for immunotherapy and molecular therapy for patients with CRC. In summary, m5C modification, an important epigenetic regulators in CRC, provides a new perspective on the mechanism underlying cancer therapy and precision medicine research. Future research should focus on revealing the specific role of m5C modification in the tumor microenvironment and drug resistance mechanisms and promote its clinical translation in diagnosis and treatment.